Muzium padi kiosk: a case study in muzium padi Kedah - Saidin, Aeni Zuhana; Alwi, Asmidah; Shaari, Nassiriah (Discovery Publication, 2018)
This paper describes the design and development of Muzium Padi Kiosk. The process was done according to the software development process.The phase started with the requirement analysis before it goes into the design and formative evaluation.Some amendment was also made at the end of the process to ensure that the kiosk will be effective and successful to deliver meaningful information to the museum visitors. As a result an interactive kiosk is ready to be used at Muzium Padi Kedah.